APPLICATION OF ECONOMIC AND MATHEMATICAL MODELING TO OPTIMIZING MANAGEMENT DECISIONS ON HUMAN CAPITAL OF AN ENTERPRISE - OSTAPCHUK, Olha; POPERETCHYI, Borys (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article aims to substantiate the application of economic and mathematical models relevant to the stages of reproduction of human capital in an enterprise (formation, utilization, development, retention or dismissal) to optimize management decisions on human capital consistent with the strategic goals of the enterprise. Integrating several areas of application of economic-mathematical modeling in human capital decision-making discussed in previous studies, the article proposes four models for application. To optimize management decisions on the human capital utilization, it is recommended to apply a model of optimal allocation of existing human resources in the form of an integer programming model for maximizing net profit. From the point of view of planning hiring, firing, and training, it is advisable to apply a model for minimizing the total costs associated with firing, recruitment and hiring, hiring non-staff personnel, and training costs. When developing an optimal human capital management strategy to achieve goals such as maximizing the number of skilled workers while minimizing the costs of training and material resources for unskilled workers, it is advisable to apply the team dynamics model, which is built on the basis of the SIR epidemic model and will form the mathematical basis of the cellular automaton simulation model. For a general understanding and assessment of the effect of human capital management practices at an enterprise, it is advisable to apply a model in the form of a system of multiple moderated regressions. The application of the described models at the enterprise will facilitate a holistic approach to human capital management.
Keywords: human capital; management; enterprise; optimization model; dynamics model; moderated regressions; system